High-performance hysteresis-free perovskite transistors through anion engineering - Huihui Zhu; Ao Liu; Kyu In Shim; Haksoon Jung; Taoyu Zou; Youjin Reo; Hyunjun Kim; Jeong Woo Han; Yimu Chen; Hye Yong Chu; Jun Hyung Lim; Hyung-Jun Kim; et al. (Nature Communications)
Abstract Despite the impressive development of metal halide perovskites in diverse optoelectronics, progress on high-performance transistors employing state-of-the-art perovskite channels has been limited due to ion migration and large organic spacer isolation. Herein, we report high-performance hysteresis-free p-channel perovskite thin-film transistors (TFTs) based on methylammonium tin iodide (MASnI3) and rationalise the effects of halide (I/Br/Cl) anion engineering on film quality improvement and tin/iodine vacancy suppression, realising high hole mobilities of 20 cm2 V−1 s−1, current on/off ratios exceeding 107, and threshold voltages of 0 V along with high operational stabilities and reproducibilities. We reveal ion migration has a negligible contribution to the hysteresis of Sn-based perovskite TFTs; instead, minority carrier trapping is the primary cause. Finally, we integrate the perovskite TFTs with commercialised n-channel indium gallium zinc oxide TFTs on a single chip to construct high-gain complementary inverters, facilitating the development of halide perovskite semiconductors for printable electronics and circuits.